Implementas Penguatan Nilai-Nilai Ketuhanan Yang Maha Esa dalam Kehidupan Sehari-Hari di SD Inpres Lasiana - Maria T. L. Ruma; Yulsy M. Nittle; Hinda Susana Nenobais; Clara Dian Mbejo Mbipi; Kevin Fernandes KLau; Yulianty Ully; Jeklina Hoar Kehi (Lembaga Pengembangan Kinerja Dosen, 2024)
Implementation is an activity or action to carry out a plan that has been made in detail to achieve a goal. The word implementation comes from English, namely to implement, which means to implement. One of the implementations that needs to be applied to the nation's children from an early age is the implementation of strengthening the values ​​of the Almighty God in everyday life, which is very important for building national character, by understanding and practicing it. With these values, we can create an environment of harmony and mutual respect. Belief in the Almighty is the basis of all religious teachings in Indonesia. This reflects unity and tolerance between religions. By implementing the values ​​of the Almighty God, we can prioritize togetherness in diversity.